2018
DOI: 10.1111/cid.12694
|View full text |Cite
|
Sign up to set email alerts
|

Use of IL‐1 β, IL‐6, TNF‐α, and MMP‐8 biomarkers to distinguish peri‐implant diseases: A systematic review and meta‐analysis

Abstract: Objective To investigate the use of peri‐implant crevicular fluid (PICF) interleukin‐1β (IL‐1β), IL‐6, tumor necrosis factor‐α (TNF‐α), and matrix metalloproteinase‐8 (MMP‐8) biomarkers in distinguishing between healthy implants (H), peri‐implant mucositis (MU), and peri‐implantitis (PI). Material and Methods Electronic using three databases (Pubmed, EMBASE, and Cochrane) and manual searches were conducted for articles published up to March 2018 by two independent calibrated reviewers. Meta‐analyses using a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 57 publications
9
94
1
1
Order By: Relevance
“…Studies have detected MMP‐8 in saliva and GCF of periodontitis patients and in PICF of PIP patients suggestive that MMP‐8 levels may be useful for diagnostic monitoring of the connective tissue destruction phase of peri‐implant disease. MMP‐8, including targeting its active form, has been reported to represent a valuable target for chairside point‐of‐care testing of oral fluids related to detection of periodontitis, and more recently in PIP; albeit active MMP‐8’s ability to affect treatment decision‐making remains to be fully elucidated and implemented within the global dental profession. Similar to our findings, Wang et al did not observe significant differences in the concentration of MMP‐8 between healthy and PIP individuals, although the literature would support that differences in selection of antibody systems to detect these types of biomolecules can create variation in the levels and outcome measures between health and disease .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have detected MMP‐8 in saliva and GCF of periodontitis patients and in PICF of PIP patients suggestive that MMP‐8 levels may be useful for diagnostic monitoring of the connective tissue destruction phase of peri‐implant disease. MMP‐8, including targeting its active form, has been reported to represent a valuable target for chairside point‐of‐care testing of oral fluids related to detection of periodontitis, and more recently in PIP; albeit active MMP‐8’s ability to affect treatment decision‐making remains to be fully elucidated and implemented within the global dental profession. Similar to our findings, Wang et al did not observe significant differences in the concentration of MMP‐8 between healthy and PIP individuals, although the literature would support that differences in selection of antibody systems to detect these types of biomolecules can create variation in the levels and outcome measures between health and disease .…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers linked to PIP include an array of pro‐inflammatory cytokines (tumor necrosis factor‐α, interferon‐γ, interleukin (IL)‐1β, IL‐6, anti‐inflammatory cytokines (IL‐4 and IL‐10), chemokines (IL‐8, monocyte chemoattractant protein (MCP)‐1 and macrophage inflammatory protein (MIP‐1α), and tissue destructive enzymes (matrix metalloproteinases (MMP‐8) . Of these, pro‐inflammatory cytokines demonstrate the strongest association with PIP . However, additional studies are needed to establish their validity, help predict susceptibility, identify early biological indicators of failing implants and better quantify response to therapy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to what was found with IL-1β, IL-6 increases significantly between PIM and PI. IL-6 links innate and acquired immune responses, in which it induces differentiation of activated B cells into antibody-producing cells as well as naïve CD4+ T cells [36]. Studies of experimental PIM demonstrated that TNFα and TGF-β2 levels did not change during an experimental PIM period.…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%
“…MMP upregulation has been associated with irreversible peri-implant connective tissue destruction [42]. One suggested reason for MMP upregulation is polymorphism in the promoter region of MMP-8 which explains varied responses between different individuals with the same disease category [36]. During the initiation and course of inflammatory responses in PI, proinflammatory mediators including MMP-8 are up-regulated in affected tissues and present in PICF [51].…”
Section: Enzymesmentioning
confidence: 99%